2012
DOI: 10.1097/ypg.0b013e3283518524
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene insertion/deletion polymorphism is not associated with schizophrenia in a Croatian population

Abstract: Because angiotensin-converting enzyme (ACE) plays an important role in dopamine system functioning in the brain and the insertion/deletion (I/D) polymorphism of a 287 nucleotide fragment of the ACE gene correlates with enzyme activity, several studies have investigated the role of the ACE I/D polymorphism in psychiatric diseases (Segman et al., 2002;Crescenti et al., 2009). Two recent studies have yielded contradictory results: the D allele was identified as a protective factor in a Spanish population, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 5 publications
3
23
1
1
Order By: Relevance
“…A meta-analysis evaluating the data of several studies indicated that there was no association between schizophrenia and ACE I/D polymorphism 25 , and the same result was supported in a study with the Croatian population 26 , in consistent with our study results. While it was reported that bipolar disorder was not associated with I/D polymorphism 27 , another study suggested that it was associated with I/D genotype in the Asian race 28 .…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis evaluating the data of several studies indicated that there was no association between schizophrenia and ACE I/D polymorphism 25 , and the same result was supported in a study with the Croatian population 26 , in consistent with our study results. While it was reported that bipolar disorder was not associated with I/D polymorphism 27 , another study suggested that it was associated with I/D genotype in the Asian race 28 .…”
Section: Discussionsupporting
confidence: 92%
“…In line with gender‐specific differences in the effect of the ACE‐I/D polymorphism in various conditions and/or diseases, such as blood pressure (among healthy individuals) (Avila‐Vanzzini et al., 2015), hypertension (Higaki et al., 2000; Sipahi, Budak, Şen, Ay1, & Şener, 2006), schizophrenia (Mazaheri, 2015; Nadalin, Buretić‐Tomljanović, Ristić, Jonovska, & Tomljanović, 2015; Nadalin et al., 2012), as well as MS (Lovrečić et al., 2006), and according to observations of gender–gene interaction in risk for nicotine dependence in general population (Beuten, Payne, Ma, & Li, 2006; Beuten et al., 2005; Nedic et al., 2010; Tochigi et al., 2007) and specific diseases (i.e., schizophrenia) (Nadalin, Buretić‐Tomljanović, Rebić, Pleša, & Šendula Jengić, 2016) association analyses between ACE‐I/D polymorphism and smoking habits were performed separately among male and female patients. Furthermore, there is also evidence that estrogen may influence dopaminergic neurotransmission, since it has been observed that estrogen treatment reduces dopamine receptor D2 levels in several rat brain regions (Chavez et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, 7 out of the 9 previous studies investigating the I/D polymorphism correlation with SCZ were negative (Arinami et al, 1996;Ouyang et al, 2001;Segman et al, 2002;Golimbet et al, 2005;Baskan et al, 2010;Nadalin et al, 2012;Song and Lee, 2014), while of the remaining 2 of the 9 studies, one reported significantly lower D-allele frequency in SCZ (Crescenti et al, 2009) and the other reported significantly lower I/I genotypes (Kucukali et al, 2010). Taken together, our results are consistent with the majority of previous studies, as we also did not find any significant association between I/D genotypes alone and SCZ diagnosis.…”
Section: Discussionmentioning
confidence: 95%